Process over outcome quality in paediatrics? An analysis of outpatient healthcare quality indicators for seven common diseases. Issue 1 (17th February 2023) - Müller, Teresa; Mehl, Claudia; Nau, Thorsten; Bachmann, Christian; Geraedts, Max
Abstract : Purpose: The purpose of this study was to examine the scope, quality dimensions and treatment aspects covered by existing quality indicators (QIs) for the somatic diseases bronchial asthma, atopic eczema, otitis media and tonsillitis as well as the psychiatric disorders attention deficit hyperactivity disorder (ADHD), depression and conduct disorder in paediatrics. Methods: QIs were identified through an analysis of the guidelines and a systematic search of literature and indicator databases. Subsequently, two researchers independently assigned the QIs to the quality dimensions according to Donabedian and Organisation for Economic Cooperation and Development (OECD) and to the content categories covering the treatment process. Results: We found 1268 QIs for bronchial asthma, 335 QIs for depression, 199 QIs for ADHD, 115 QIs for otitis media, 72 QIs for conduct disorder, 52 QIs for tonsillitis and 50 QIs for atopic eczema. Of these, 78% focused on process quality, 20% on outcome quality and 2% on structural quality. Using OECD criteria, 72% of the QIs were assigned to effectiveness, 17% to patient-centredness, 11% to patient safety and 1% to efficiency. The QIs covered the following categories: diagnostics (30%), therapy (38%), patient-reported outcome measures/ observer-reported outcome measures/patient-reported experience measures (in sum 11%), health monitoring (11%) and office management (11%). Conclusion: Most QIs focused on the dimensions of effectiveness and process quality, and on the categories of diagnostics and therapy, with outcome-focused and patient-focused QIs being under-represented. Possible reasons for this striking imbalance could be the easier measurability and clearer assignment of accountability in comparison to the QIs of outcome quality, patient-centredness and patient safety. To produce a more balanced picture of the quality of healthcare, the future development of QIs should prioritise the currently under-represented dimensions.